Urban Agriculture Program: the Intention of Participants to Remain As Volunteers - Ramalingam, Leelanayagi; Sharifuddin, Juwaidah; Abidin Mohamed, Zainal; Ali, Fazlin (International Journal of Engineering and Technology, 2018)
Community Garden Program is a program where people from a residential area practice urban agriculture together in a common place. Production of crop and livestock within cities is known as urban agriculture. Community Garden Program is one of the most popular initiatives by the Malaysian government in enhancing urban agriculture. Nevertheless, the program is facing challenges in attracting and retaining the volunteers. This article aims to identify the association between socio-eco-demographic characteristics and intention to remain as a volunteer for Urban Agriculture Program. The survey was conducted among 375 volunteers in Klang Valley using questionnaire. Descriptive analysis, reliability analysis and chi-square test for independence analysis were conducted. The result from descriptive analysis shows that most participants have the intention to remain as volunteers. The Cronbachâ€™s Alpha test specified that the internal consistency of intention to remain items was excellent. Chi-square test for independence indicated that elder male with high income is more likely to remain as volunteers for the Urban Agriculture Program. This study expands the existing literature on volunteerism among the urban dweller regarding participating in community-based Urban Agriculture Program.Â Â